Crystallization and preliminary X-ray analysis of peptidyl-tRNA hydrolase from Thermus thermophilus HB8 - Matsumoto, Ami (International Union of Crystallography, 2013)
Peptidyl-tRNA is produced from the ribosome as a result of aborted translation. Peptidyl-tRNA hydrolase cleaves the ester bond between the peptide and the tRNA of peptidyl-tRNA molecules, to recycle tRNA for further rounds of protein synthesis. In this study, peptidyl-tRNA hydrolase from Thermus thermophilus HB8 (TthPth) was crystallized using 2-methyl-2,4-pentanediol as a precipitant. The crystals belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 47.45, b = 53.92, c = 58.67 Å, and diffracted X-rays to atomic resolution (beyond 1.0 Å resolution). The asymmetric unit is expected to contain one TthPth molecule, with a solvent content of 27.13% (V (M) = 1.69 Å(3) Da(−1)). The structure is being solved by molecular replacement.